The importance of feeding during milking and take off level for milking efficiency and milk production - Stadtmuller, Larissa (SLU/Dept. of Animal Nutrition and Management (until 231231), 2014)
Milking efficiency is of importance in the modern dairy production with increasing herd sizes and growing automation, such as automatic milking systems. Since the first implementation of AMS previous studies tested different take off level settings for improving milking efficiency. However, more knowledge about optimal settings for completion of milking is still relevant. The objective of this study was to determine how the combination of feeding during milking and cluster take off level shall be practiced for efficient milking in sustainable dairy production. This was tested by examining two different take off level settings combined with improved pre-stimulation by the use of feeding concentrate during milking or no feeding during milking over a four-week experiment. A 4x4 Latin square experimental design was used with four different treatments and four periods. Each period had a duration of seven days. 32 mixed-age Swedish red cows were divided into four groups balanced for milk yield, lactation number and lactation stage. Each cow went through all of the following treatments at whole udder level: cluster take off at a milk flow at 800 g/min and feeding concentrate during milking (800/f), cluster take off at 800 g/min and no feeding during milking (800/nf), cluster take off at 200 g/min and feeding during milking (200/f) and cluster take off at 200 g/min and no feeding during milking (200/nf). Measurements included individual cow milk yield, milking duration, average peak and mean milk flow and milking interval. At the end of each treatment period milk samples were collected and analysed on milk composition, SCC, Na, K, FFA content, MFG size, MFG stability and FAC. For determination of udder emptying residual milk was collected on the last day of each period and analysed on the same parameter as regular milk. The determination of residual milk took place with an intramuscular oxytocin injection after the regular milking. The combination of feeding during milking and take off level affected only the milking interval, where cows had the longest milking interval in the 200/nf treatment. Cows that received the feeding during milking treatment had a significantly higher daily milk yield a lower milking interval and a higher fat yield/milking. FFA content and MFG stability were decreased with the feeding concentrate during milking treatment. Residual milk yield increased with higher take off level. Treatments with higher take off level showed as well a milking time reduction of 42 seconds per cow. A higher take off level setting combined with feeding during milking had no negative effects on milk yield, milk quality and udder emptying. Due to a reduced milking time and elevated milk yield of that treatment it has to be considered as possibility to improve the milking efficiency.